Obtenção, caracterização e aplicação de solventes eutéticos profundos na extração de compostos fenólicos presentes no resíduo do abacaxi (Ananas comosus) - Costa, Willyan Araújo da (2023)
The search for new analytical methods is a current reality in the analytical chemistry area. Among the applied approaches, the use of green solvents presents several highlights. In this context, the use of deep eutectic solvents (DESs) as an alternative have been receiving detach. Thus, the present work aimed to evaluate the mainly chemical, physical-chemical and ecotoxic properties of seven different DESs and to apply them for the extraction and quantification of phenolic compounds present in the pineapple (Ananas comosus) industrial waste. In the first stage, the results about the composition and their properties are presented. As result, it was observed that DESs viscosities is directly dependent on the precursor structures and intermolecular interactions. About the superficial tension, this property fallowed the same tendency of the viscosity, however, strongly sensitive to the water addition. The rheological profiles of the solvent ChCaLa showed to be sensitive to the water addition once an addition of 10% lead the system to change from a Newtonian to a pseudo-plastic. In relation to the ecotoxic profile, the solvents based on acid HBDs presented a superior inhibition capacity than others, been the ChGy presented the lower inhibition capacity. About the bactericide profile, the most hydrophobic DESs (PtGyLa and OcGyLa) presented the higher dangerous effect, while binaries systems presented the lower. In the second part, the results about the usage of ternary DESs as extractor agents of phenolic compounds from pineapple waste samples, followed by their quantification by spectrophotometry at UV-Vis region. The preliminary data showed that solvent ChGuLa presented the better extractive action, in terms of total phenolic content (109.30 ± 9.06 mgEAG g-1sample), been this result corroborated by the solid samples characterization in terms of its lignin content, Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). At least, the developed method optimization was carried out by a central composite design (CCD), where the process main variables (water addition, extraction time, temperature, and sample mass) were investigated. The best condition (226.37 30 ± 9.50 mgEAG g-1sample) was achieved by the addition of 35% of water and a solvent volume of 3 mL for the extraction using 0.15 g of sample at 65 ºC during 90 min, been this result superior to the obtained using a conventional hydroetanolic solution at 70% v v-1 (190.53 ± 9.37 mgEAG g-1sample), what reinforce the usage of DESs as extractor agents.